Buddhism in Taiwan: Religion and the State, 1660-1990. Charles Brewer Jones. - Tarocco, Francesca (Buddhist Studies Review, 2002)
Buddhism in Taiwan: Religion and the State, 1660-1990. Charles Brewer Jones. University of Hawai’i Press, Honolulu 1999. xviii, 259 pp. 46.00. ISBN 0-8248-2061-4.